2022
DOI: 10.1007/s00415-022-11224-6
|View full text |Cite
|
Sign up to set email alerts
|

The clinical relevance of serum versus CSF NMDAR autoantibodies associated exclusively with psychiatric features: a systematic review and meta-analysis of individual patient data

Abstract: Background A variety of psychiatric syndromes are associated with NMDAR autoantibodies; however, their clinical relevance when only present in the serum is unclear. We explored whether patients with CSF NMDAR autoantibodies could be distinguished from patients with serum-only NMDAR autoantibodies. Methods The electronic databases MEDLINE, EMBASE, PubMed, and PsycINFO were searched. Articles reporting adult patients with isolated psychiatric feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The onset of NMDARE is often characterized by psychiatric symptoms [ 5 , 6 ]. Nevertheless, NMDAR autoantibodies are also detected in psychiatric patients who fail to fulfill NMDAR-encephalitis criteria [ [7] , [8] , [9] ]. The role NMDAR autoantibodies play in these patients is less well understood, and deserves investigation in large-scale studies.…”
Section: Nmdar Autoantibodies In Psychiatrymentioning
confidence: 99%
See 2 more Smart Citations
“…The onset of NMDARE is often characterized by psychiatric symptoms [ 5 , 6 ]. Nevertheless, NMDAR autoantibodies are also detected in psychiatric patients who fail to fulfill NMDAR-encephalitis criteria [ [7] , [8] , [9] ]. The role NMDAR autoantibodies play in these patients is less well understood, and deserves investigation in large-scale studies.…”
Section: Nmdar Autoantibodies In Psychiatrymentioning
confidence: 99%
“…It is essential to examine autoantibodies against NMDAR NR1 in CSF as well as serum, because their presence in CSF with typical clinical features supports the diagnosis of definite autoimmune encephalitis according to the Graus criteria [ 4 ]. In addition, a recent study by Blackman [ 9 ] demonstrated that psychiatric syndromes associated with NMDAR antibodies can differ from psychiatric syndromes associated with serum NMDAR antibodies on the basis of clinical demographic factors and diagnostic features. For example, patients presenting CSF NMDAR antibodies unlike those with serum NMDAR antibodies) were more likely to suffer a subacute onset, more likely to be female, more likely to present EEG and CSF abnormalities, and more likely to be psychotic and suffer from insomnia [ 9 ].…”
Section: Nmdar Autoantibodies In Psychiatric Autoimmune Encephalitismentioning
confidence: 99%
See 1 more Smart Citation
“…antibody detection (54). Interestingly, in a prior validation study of a commercial diagnostic kit based on indirect immunofluorescence on transfected cells, a false-positive rate of 1.4% has been reported for the application of serum and cell-based assay (55).…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is based on the observation that in encephalitides associated with antibodies and intracellular antigens, CD8+ T cells were frequently found in encephalitic brain tissue [ 1 ]. The other major mechanism is characterized by the action of neural autoantibodies, such as antibodies against the N-methyl-D-aspartate receptor [ 2 ] detected in an autoimmune encephalitis of psychiatric phenotype [ 3 ]. Neural autoantibodies are part of the immune defense, which can play a protective role in destroying cancer (as paraneoplastic antibodies on the one hand), but they can also be destructive when accompanying CNS inflammation and neuronal nerve cell damage [ 4 ].…”
Section: Introduction—immunological Conception Of Central Nervous Sys...mentioning
confidence: 99%